Strategies for Adapting to Climate Change by Livestock Farmers in Southwestern Nigeria - L.T, Ogunniyi; O.D, Komolafe; A.A, Adepoju; G.E, Fanifosi (International Journal of Climate Research, 2020)
Livestock production sector is one of the area in agriculture which is sensitive to climate change effect. In quest to unveil the coping mechanism adopted by farmers to mitigate the effect climate change imposes on livestock production, this study however examined farmers’ strategies for adapting to climate change by livestock farmers in South-western Nigeria. Specifically, it identifies the various adaptation techniques adopted to mitigate the perceived effect of climate change, as well as the effect of climate change on livestock production and adaptation strategies. Data were collected using well-structured questionnaire and interview schedule administered on 120 farmers through the use of multistage sampling procedure in the study area. Descriptive statistics and multinomial Logit were used to analyze data collected. The multinomial Logit model used to analyze the determinants of farm-level adaptation measures revealed that age, sex, farm size and experience are statistically significant at various levels. The adaptation measure used are moving focus from livestock to crop, adopting drought tolerant animal, investing in multiple livestock species and engaging in nonfarm activities. Priority should be set on adjusting to ongoing and potential effects of climate change, deforestation and bush burning should be discourage and lastly adoption of new technologies to improve production will help reduce the effect of climate change.